Validity of cycloheximide chylomicron flow blocking method for the evaluation of lymphatic transport of drugs - Ryšánek, Pavel; Grus, Tomáš; Lukáč, Peter; Kozlík, Petr; Křížek, Tomáš; Pozniak, Jiří; Roušarová, Jaroslava; Královičová, Jana; Kutinová Canová, Nikolina; Boleslavská, Tereza; Bosák, Jan; Štěpánek, František; et al. (British journal of pharmacology, 2021)
BACKGROUND AND PURPOSE: Lymphatic transport of drugs after oral administration is an important mechanism for absorption of highly lipophilic compounds. Direct measurement in lymph duct cannulated animals is the gold standard method, but non-invasive cycloheximide chylomicron flow blocking method has gained popularity recently. However, concerns about its reliability have been raised. The aim of this work was to investigate the validity of cycloheximide chylomicron flow blocking method for the evaluation of lymphatic transport using model compounds with high to very high lipophilicity, that is, abiraterone and cinacalcet. EXPERIMENTAL APPROACH: Series of pharmacokinetic studies were conducted with abiraterone acetate and cinacalcet hydrochloride after enteral/intravenous administration to intact, lymph duct cannulated and/or cycloheximide pre-treated rats. KEY RESULTS: Mean total absolute oral bioavailability of abiraterone and cinacalcet was 7.0% and 28.7%, respectively. There was a large and significant overestimation of the lymphatic transport extent by the cycloheximide method. Mean relative lymphatic bioavailability of abiraterone and cinacalcet in cycloheximide method was 28-fold and 3-fold higher than in cannulation method, respectively. CONCLUSION AND IMPLICATIONS: Cycloheximide chylomicron flow blocking method did not provide reliable results on lymphatic absorption and substantially overestimated lymphatic transport for both molecules, that is, abiraterone and cinacalcet. This non-invasive method should not be used for the assessment of lymphatic transport and previously obtained data should be critically revised.
Keywords: intestinální absorpce; Animals; biologický transport; Cycloheximide; Intestinal Absorption; Biological Availability; Reproducibility of Results; biologická dostupnost; Pharmaceutical Preparations; léčivé přípravky; Biological Transport; cykloheximid; reprodukovatelnost výsledků; chylomikrony; aplikace orální; krysa rodu Rattus; Administration, Oral; zvířata; Chylomicrons; Rats